The mechanism and dynamics of the sedimentation of styrene/divinylbenzene microplastics from water and the solidification of the precipitate with an alum-based coagulant “BUCOCHEM” - Vasyl Kulish; Sergiy Boruk; Igor Winkler (PLoS ONE, 2026)
Although publications on the efficiency of various coagulants in removing microplastic contamination from water are quite abundant, detailed information on the coagulation/sedimentation mechanisms and dynamics, and on the formation of microplastic particle flocs, is less common. In this article, the mechanism and dynamics of coagulation, flocs formation, and sedimentation of styrene/divinylbenzene microplastic particles sized between 400 and 500 µm from water with the use of an alum-based coagulant “BUCOCHEM” have been investigated. The research has been conducted using jar tests to study coagulation/sedimentation dynamics and visual microscopic observations to examine floc formation. It was found that this coagulant promotes better sedimentation and compaction of the plastic particles, ensuring the formation of a dense, more stable, and easily removable precipitate layer. A 0.1 wt % of the coagulant leads to a decrease in the height of the polymer sediment layer by 14% after 48 hours, as compared to the coagulant-free sedimentation. Furthermore, the former sediment appears more compact and stable. Even the lower 0.05–0.07 wt% of BUCOCHEM ensures the formation of three-dimensional flocs, which sediment into a compact and stable precipitate layer, effectively resisting secondary resuspension. Although such concentrations of BUCOCHEM lead to some decrease in the sedimentation rate (from 3.5 to 2.5–2.7 mm/s), it is more important that the resulting precipitate layer becomes more compact and stable against secondary resuspension than without the coagulant. The process of the precipitate layer compacting and solidification is mostly complete within 24 h. These results indicate the most optimal concentration of BUCOCHEM (0.05–0.07 wt%) and seem useful for potential application of this coagulant to treat water/wastewater for the removal of microplastic contamination.